PENGARUH PENERAPAN ISO 9001: 2008 TERHADAP KINERJA PEGAWAI (Survei pada Pegawai Dinas Kependudukan dan Pencatatan Sipil Surakarta) - Okprida Kusuma, Yoneza Ayu; Lamidi, Lamidi; Sri Utami, Setyaningsih (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2018)
The objective of this research is to analyze the effect of the application of ISO 9001: 2008 on the performance of employees at the Dinas Kependudukan dan Pencatatan Sipil Surakarta. The population in this study were 49 employees. Data collection methods used: questionnaires, analysis techniques used validity test, reliability test, classic assumption test, descriptive analysis, multiple linear regression analysis, t test, F test, and determination coefficient. The results of descriptive analysis of the quality management system, management responsibilities, resource management, product realization, measurement, analysis and improvement are said to be good categories, it shows that the performance of employees is in good condition. The results of partial hypothesis testing of resource management and measurement, analysis and improvement have a significant effect on employee performance, while the quality management system, management responsibilities, and product realization have no significant effect on employee performance. The results of testing hypotheses silmutan quality management systems, management responsibilities, resource management, product realization, measurement, analysis and improvement have a significant effect on the performance of employees in the Dinas Kependudukan dan Pencatatan Sipil Surakarta.Keywords: Quality Management System, Management Responsibility, Resource Management, Product Realization, Measurement, Analysis and Improvement, Employee Performance.